Evaluation of Endotracheal Tube Cuff Pressure in Laparoscopic Cholecystectomy and Postoperative Sore Throat - Lakhe, Gajal; Sharma, Surendra Mohan (Journal of Nepal Health Research Council, 2018)
Background: The use of nitrous oxide and carboperitoneum in laparoscopic cholecystectomy lead to increase in endotracheal tube cuff pressure. It may impair tracheal mucosal perfusion with subsequent tracheal damage. The purpose of this study was to evaluate cuff pressure and incidence of post-operative sore throat in patients undergoing laparoscopic cholecystectomy. Methods: In this prospective observational study, 128 patients aged 18-65 years of American Society of Anesthesiologist physical status I and II undergoing laparoscopic cholecystectomy were enrolled and allocated alternately into two groups, Study Group (Maintenance of anesthesia with sevoflurane 1-2%, oxygen/nitrous oxide mixture; 40/60), Control Group (Maintenance of anesthesia with sevoflurane 1-2%, oxygen/air mixture; 40/60) were analysed and comapared. Each group contained 64 patients. Aneroid manometer was used to monitor cuff pressure. Volume of air used to inflate the cuff, baseline cuff pressure, comparison of intraoperative cuff pressure and incidence of postoperative sore throat were measured. Results: The study results demonstrated higher cuff pressure in study group at all times after the creation of carboperitoneum (p=0.00) with increased incidence of sore throat(p=0.004). Conclusions: Increase in endotracheal tube cuff pressure was noted with the use of nitrous oxide in laparoscopic cholecystectomy with subsequent post-operative airway complication. Monitoring of cuff pressure is simple, noninvasive and efficient way of achieving therapeutic cuff pressure of 20-30 cm of H2O and thus recommends its use.